Minimally Invasive Posterolateral Approach for Surgical Resection of Dumbbell Tumors of the Lumbar Spine - Kerimbayev, Talgat T.; Tuigynov, Zhandos M.; Aleinikov, Viktor G.; Urunbayev, Yermek A.; Kenzhegulov, Yergen N.; Baiskhanova, Dinara M.; Abishev, Nurzhan B.; Oshayev, Meirzhan S.; Solodovnikov, Makar P.; Akshulakov, Serik K. (Frontiers in Surgery, 2022)
Minimally invasive spine surgery (MISS) has many advantages over traditional open surgical procedures. The aim of the study was to evaluate institutional experience with Dumbbell tumors and metastatic lesions of the lumbar spine and compare it with traditional open surgical resection of this type of tumors. 14 patients underwent the surgery with minimally invasive posterolateral approach in experimental group, and 10 patients of the control group were operated using the traditional open surgery procedure at the Department of spinal neurosurgery and pathology of peripheral nervous system of JSC "National Center for Neurosurgery". The experimental group included 14 patients, that underwent the surgery during the period from January 2020 till March 2021. And the control group included 10 patients that was operated from January 2018 to December 2019. The results of the treatment in both groups were assessed according to the generally accepted visual analogue scale (VAS) and the Oswestry scales before, on the third day, and three months after the surgery. In experimental group, average reduction of the pain syndrome of 3.36 points (from 3 to 0 points) was observed in patients postoperatively according to the VAS 3 days, and of 4.0 points (from 2 to 0 points) 3 months after surgical procedures. Improvement by 23.86% (36% to 16%) was also observed using the Oswestry Disease Index (ODI) 3 days after the surgery, and then reduced to 21.00% (16% to 34%) in average in 3 months. All patients were revived 3 hours after transfer to the specialist department. The average stay in the hospital was 6.5 (9 to 4) days in both groups. In control group, average reduction of the pain syndrome of 2.60 points (from 4 to 1 points) was observed postoperatively according to the VAS 3 days after the operation, and of 3.9 points (from 2 to 0 points) 3 months after the surgery. The ODI of patients was also improved by an average of 35.40% (50% to 20%) 3 days after the surgical procedure, and reduced to 24.20% (16% to 32%) in average 3 months after the surgery.